Transplantation and Pregnancy - Erkan Uc, Pinar; Sagol, Sermet (Gynecology Obstetrics & Reproductive Medicine, 2024)
Transplantation is becoming increasingly widespread worldwide as a life-saving treatment for patients with end-stage organ failure. While the woman's quality of life improves rapidly after transplantation, the improvement of the endocrine system helps to regain fertility. The success of conception and successful pregnancy rates are quite low compared to the general population. Particular attention should be paid to obstetric complications such as hypertension, preeclampsia, fetal growth restriction, and preterm delivery during pregnancy. Ideally, preconception counseling should begin in the period before transplantation. Initiating contraception immediately after transplantation is ideal and long-acting reversible methods such as intrauterine devices and subcutaneous implants may be preferable. Factors that influence pregnancy outcomes in women undergoing organ transplantation include good general health within two years of transplantation, no evidence of organ rejection in the last year, stable graft conditions, absence of acute infections affecting the fetus, and adequate doses of immunosuppression drugs. However, factors that may adversely affect pregnancy include the etiology of the disease requiring transplantation, chronic allograft dysfunction, renal failure, cardiopulmonary diseases, hypertension, diabetes, obesity, and infections such as hepatitis B, hepatitis C, and Cytomegalovirus (CMV). Postponing pregnancy for at least 1 year after transplantation is very important to optimize pregnancy outcomes. Pregnancy in the early post-transplant period increases the risk of acute rejection, infection risk, and graft-related problems. In general, transplanted women can have successful pregnancies and live birth rates are above 70% on average. Although perinatal morbidity and mortality rates are high, most newborns are healthy and develop normally. Specific criteria such as pre-pregnancy serum creatinine levels and blood pressure control, as well as adherence to immunosuppressive therapy, significantly influence pregnancy success in transplant patients. In this review, optimizing pregnancy outcomes often involves addressing maternal and fetal risks, regular graft monitoring to detect potential complications such as organ rejection, and regulation of transplant medications to ensure safety and efficacy during pregnancy. Successful management relies on a multidisciplinary approach with contributions from obstetricians, neonatologists, nephrologists, hepatologists, and transplant surgeons.